MODEL ACCELERATED LEARNING IN ENHANCING LEARNING ABILITIES OF PARTICIPANTS - Rahman, Nur Amalina Abdul; Muis, Andi Abd.; Wahyuni, Mardiah; Risqullah, Nur Aisyah; Heriani, Heriani (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to determine the improvement of students' learning abilities through the implementation of the Accelerated Learning model. The method used in this research is a qualitative descriptive approach with a library research study type. The results of this research show that in the learning activities, students face differences in their abilities to grasp the lesson materials. The characteristics of students vary, with some having above-average abilities in receiving lesson materials, some having average abilities, and some below-average in receiving lessons. Therefore, there is a need for innovative learning methods to enhance students' learning abilities. Accelerated Learning emerges as a model to create enjoyable learning activities. The Accelerated Learning model aims to establish a pleasant learning environment without the pressure felt by students, and it occurs rapidly, effectively, and efficiently.